From Conventional Tourism to Sharia Tourism: Achievements and Requirements - Linda Sari Bulan Siregar; Tiara Rahayu; Mardianton Mardianton; Zulhijatul Rahmi; Supardi Dwimaputra; Marizem Munir (Journal of Islamic Economics and Finance Studies, 2025)
The global tourism industry has seen significant growth, including in Indonesia. However, as Muslim awareness of Sharia principles increases, there is a growing need for alternative forms of tourism that not only offer entertainment but also align with Islamic values. This article discusses the paradigm shift from conventional tourism to Sharia tourism. The researcher used the library research method, which involves reviewing, analyzing, and examining data obtained from various written sources relevant to the research topic. Library research aims to obtain a theoretical foundation and in-depth understanding of the issues being studied through literature sources, including concepts, implementation, and challenges faced. Conventional tourism often does not consider aspects of halal-haram, modesty boundaries, and interactions between the sexes, whereas Islamic tourism emerges as a solution by prioritizing Islamic ethical principles in all tourism activities. The study indicates that Islamic tourism has significant potential as an alternative tourism model that not only attracts Muslim tourists but also fosters the growth of a sustainable halal industry. However, this transition requires collaboration between the government, industry players, and the community to be realized optimally.